1999
DOI: 10.1557/proc-558-491
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Resolved Photoluminescence (PL), Delayed Fluorescence and Triplet-Triplet Annihilation in Φ-Conjugated Polymers

Abstract: The delayed fluorescence of poly(p-phenylene vinylene) (PPV) and poly(p-phenylene ethynylene) (PPE) derivative solids and frozen solutions at 20 K is described. It provides strong evidence for triplet-triplet annihilation to singlets excitons accounting for up to ∼3% of the total emission in PPV films and ∼1.5% in PPE powder. It also yields triplet lifetimes of 70 and 110 μs in PPV films and frozen solutions, and ∼200 and ∼500 μs in PPE powder and frozen solutions, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The mechanism for the T 1 → S 1 transition may involve a second inelastic tunnelling process, , possibly via an initial transition to a higher lying state in the triplet manifold for which it has been shown that intersystem transfer may be more rapid . Alternatively, this transition may involve a TTA process . In our recent studies of triplet emission from a small molecule it was possible to rule out TTA as a mechanism, but in the absence of direct triplet emission in our devices we are unable to discriminate between these possible mechanisms and in addition note that Thomas et al .…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The mechanism for the T 1 → S 1 transition may involve a second inelastic tunnelling process, , possibly via an initial transition to a higher lying state in the triplet manifold for which it has been shown that intersystem transfer may be more rapid . Alternatively, this transition may involve a TTA process . In our recent studies of triplet emission from a small molecule it was possible to rule out TTA as a mechanism, but in the absence of direct triplet emission in our devices we are unable to discriminate between these possible mechanisms and in addition note that Thomas et al .…”
Section: Resultsmentioning
confidence: 66%
“…51 Alternatively, this transition may involve a TTA process. 52 In our recent studies of triplet emission from a small molecule it was possible to rule out TTA as a mechanism, but in the absence of direct triplet emission in our devices we are unable to discriminate between these possible mechanisms and in addition note that Thomas et al 53 have shown that the triplet population can be affected by J-type aggregation in P3HT further complicating a comparison with previous studies of electroluminescence from a molecular monolayer.…”
Section: Resultsmentioning
confidence: 68%
“…Historically, contributions of this bimolecular channel have been inferred from delayed fluorescence, though it is the least likely of all annihilation channels. 29 Additionally, pulse radiolysis investigations of solvated polymers represent a substantial body of work in the study of triplets and their interactions, where it has been suggested that a single polymer chain (i.e., high molecular weight (M W )) may support up to 30 triplets at a time. 30 Table 1 presents a brief summary of relevant excitonic processes with their respective rate constants used in the coupled photodynamic model.…”
Section: Triplet Processes At the Single Moleculementioning
confidence: 99%
“…Whereas such nonradiative quenching of singlets is simple to study by considering the photoluminescence (PL) yield or PL lifetime, investigating the quenching of triplets requires either phosphorescence 6 or photoinduced absorption measurements, 7 or an inspection of delayed fluorescence arising from triplet−triplet annihilation. 8 Magnetic resonance techniques can also be used, since the triplets are characterized by a distinct spin-1 resonance feature. 9 However, detection of changes to the triplet population then typically occurs by a secondary observable, the change in PL from the singlet population, which in turn is modified due to the singlet−triplet quenching mechanism in ensemble measurements.…”
mentioning
confidence: 99%
“…Both types of excitation may pass their energy to the charge in a Coulombic process not dissimilar to Auger recombination in semiconductors, lowering the binding energy of the charge to the molecule and potentially triggering chemical reactions. Whereas such nonradiative quenching of singlets is simple to study by considering the photoluminescence (PL) yield or PL lifetime, investigating the quenching of triplets requires either phosphorescence or photoinduced absorption measurements, or an inspection of delayed fluorescence arising from triplet–triplet annihilation . Magnetic resonance techniques can also be used, since the triplets are characterized by a distinct spin-1 resonance feature .…”
mentioning
confidence: 99%